THE ROLE OF AUDITING PROFESSION IN DETECTING FRAUDS IN FINANCIAL STATEMENTS - Knežević, Snežana; Mitrović, Aleksandra; Cvetković, Dragan (NBP. Nauka, bezbednost, policija, 2019)
Bearing in mind the increasingly complex economic environment and the emergence of new types of fraud, it is important to see what role the audit profession plays in detectingfraud and providing reasonable persuastion about fraud. The aim of this paper is to explain how the process of auditing financial statements works. The paper distinguishes between an auditor, a fraud auditor and a forensic accountant. The similarities and differences between these professions and their interrelationships are specified. The methodology used in the paper is content analysis. The results of the analysis revealed that audit and forensic accounting are inextricably linked in detection of fraudulent actions.